Intestinal helminths in Iberian wolves (Canis lupus signatus) from Northwest Spain - Muñoz, Sara; Ramos, Pedro Luis; Carretón Gomez, Elena; Diosdado, Alicia; González-Miguel, Javier; Simón, Fernando; Morchón, Rodrigo (The Open Parasitology Journal, 2018)
Background: We present a study about helminth parasites in wolf (Canis lupus signatus) from Sierra de la Culebra, a protected area in the Northwest of Spain, where is the largest population of wolves of the Spanish territory and one of the largest in Western Europe. Materials and Methods: To this aim, 93 fecal samples were collected during May and June of 2013 using 33% zinc sulphate flotation technique and classified based on their morphology, color, structure and size. Results: Parasites were present in 66.67% of the samples and classified as Eucoleus aerophilus (50.54%), Strongyloides sp. (27%), Ancylostomidae gen. sp. (19.35%), Toxocara Canis (10.75%), Taeniidae gen. sp. (9.68%), Trichuris vulpis (9.68%) and Toxascaris leonina (2.15%). Their distributions were very heterogeneous with the highest prevalence being in Northwest Spain. These differences found can be attributed to local environmental factors (ambient temperature, humidity) as well as animal feeding and social behavior. Conclusion: A wide helminthofauna is observed in the studied wolves, similar to other studies carried out in Europe (Estonia, Finland, Italy, Latvia, Poland, Portugal, Spain and Sweden). In addition, this study constitutes the first description of the presence of Strongyloides sp. in Iberian wolf in Spain.